Have the Implementation of Financial Application Sys-tem and Management of State Property Improved Fi-nancial Report Quality in Indonesia? - Karsam, Karsam; Ariyanto, Stefanus; Putro, Dian Permana (Universitas Syiah Kuala, 2019)
Objective The objective of this study is to investigate the influence of the implementation of SIMAK system at agency level and management of state property on financial report quality of Indonesian Ministry of Finance work units.Design/methodology The study was carried out involving Finance Department of Republic of Indonesia Ministry for the period of 2017 until 2019. The samples selection of Department in Finance Ministry was based on certain criteria. The data was collected from questionnaires that were filled by staff and operator in the departments of Finance Ministry. In total, there were seventy respondents with 100% response rate. Multiple regression approach was used to analyze the survey results.Results This study demonstrates that implementation on SAKTI system and management of state property has an impact on financial report quality of department in Finance Ministry. This finding implies that the easier use of the fixed asset module in the application will make the process of preparing financial statements accurate and in accordance with the application of government accounting standards. Furthermore the better the role and function of BMN managers in administering assets will improve financial reports quality in the presentation of assets in a complete and reliable manner. Research limitations/implications - This research is limited to the subject of the Ministry of Finance work units, in which the characteristics and activities of this research subject are specific. The analysis unit/respondents that are selected in this study were limited to work units that are represented only by staff and operators.